IDENTIFICATION OF CHEMICAL COMPOUNDS FROM THE ETHANOLIC EXTRACT OF THE BARK OF BAUHINIA TOMENTOSA L. BY GC-MS ANALYSIS (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
The bark of Bauhinia tomentosa L. is used wildly used for the treatment of varies ailments such as inflammation, wound, dysentery, skin diseases and for microbial infections. In the present study the ethanolic extract of the bark of Bauhinia tomentosa L. has been subjected to Gas Chromatography-Mass Spectrometry (GC-MS) analysis, while the mass spectra of the compounds found in the extract was matched with the National Institute of Standards and Technology (NIST) library. GC-MS analysis revealed the presence of fourteen phytochemical constituents, These compounds were identified by comparing their retention time and peak area with that of literature and by interpretation of mass spectra. The major chemical constituents are 4-(Benzyloxy)-1-methoxy-2-(3,7-dimethylocta-2,6-dienyl)-benzene (10.88%), Levodopa (6.39%) and (9E, 12E) - Methyl octadeca-9,12-dienoate (5.68%) which possess many biological activities. Hence these studies pave a platform to screen many bioactive components for wound healing.